Uncivil war : the Israel conflict in the Jewish community - Kahn-Harris, Keith 1971- (David paul, 2014)
"Keith Kahn-Harris explores the cause of the conflicts over Israel, the different viewpoints and shares his unique experience of bringing together prominent British Jews with diverse opinions to his home over dinner"--Book cover